2014
DOI: 10.1128/iai.01893-14
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation and Immunoreactivity of the Histoplasma capsulatum Cfp4 Yeast-Phase Exoantigen

Abstract: The yeast phase of Histoplasma capsulatum is the virulent form of this thermally dimorphic fungal pathogen. Among the secreted proteome of Histoplasma, culture filtrate protein 4 (Cfp4) is a heavily glycosylated factor produced abundantly and specifically by Histoplasma yeast cells, suggesting its role in pathogenesis. We have generated three monoclonal antibodies as tools for characterization and detection of Cfp4 and determined the epitope each recognizes. Through site-directed mutagenesis of Cfp4, we identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
(50 reference statements)
0
12
0
1
Order By: Relevance
“…We previously observed that many known virulence factors are Ryp-associated [2]; consistent with this observation, the 16 Ryp-associated yeast-specific genes include 2 virulence factors, CBP1 [2124] and CTR3 [25], as well as two genes required for efficient lysis of macrophages, LDF1 and a gene previously designated as UA35-G3 [26]. Several others are putative secreted factors of unknown function, including the paralogs Yps21 [27] and GH17/Cfp4 [28, 29] as well as ucsf.hc_01.G217B.05476 which, along with UA35-G3, is predicted to be a secreted knottin (cystine knot proteins that show yeast-specific expression and may play a role in virulence in H. capsulatum ) [4]. Notably, these yeast-associated genes, which are normally expressed by wild-type yeast cells at 37°C, are expressed in the yeast-locked msb2 mutant even at room temperature, suggesting that their expression can be unlinked to temperature but remains linked to cell morphology.…”
Section: Resultsmentioning
confidence: 90%
“…We previously observed that many known virulence factors are Ryp-associated [2]; consistent with this observation, the 16 Ryp-associated yeast-specific genes include 2 virulence factors, CBP1 [2124] and CTR3 [25], as well as two genes required for efficient lysis of macrophages, LDF1 and a gene previously designated as UA35-G3 [26]. Several others are putative secreted factors of unknown function, including the paralogs Yps21 [27] and GH17/Cfp4 [28, 29] as well as ucsf.hc_01.G217B.05476 which, along with UA35-G3, is predicted to be a secreted knottin (cystine knot proteins that show yeast-specific expression and may play a role in virulence in H. capsulatum ) [4]. Notably, these yeast-associated genes, which are normally expressed by wild-type yeast cells at 37°C, are expressed in the yeast-locked msb2 mutant even at room temperature, suggesting that their expression can be unlinked to temperature but remains linked to cell morphology.…”
Section: Resultsmentioning
confidence: 90%
“…To confirm the function of Histoplasma Pmt proteins in protein glycosylation, secreted proteins were examined for the loss of protein glycosylation by reduction of protein molecular mass. The glycoprotein Cfp4 ( 8 , 21 ) and β-glucanases Eng1 and Exg8 ( 8 ) contain mucin-like domains in the primary amino acid sequence, suggestive of regions potentially modified by O-linked mannosylation ( 22 ). Consistent with O-mannosylation of Cfp4, the electrophoretic mobility of the Cfp4 protein is reduced by approximately 2 kDa when produced by Pmt2-deficient yeast cells, and the higher molecular mass is restored by PMT2 complementation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Culture filtrate proteins from wild-type ( PMT2 ) or mutant ( pmt2 ) yeast cells were treated with PNGase F (New England Biolabs) to remove N-linked glycans and then separated under reducing conditions by 10% SDS-polyacrylamide gel electrophoresis and transferred to nitrocellulose membranes. Proteins were detected with monoclonal antibodies to Cfp4 (clone 2D20) ( 21 ) and Sod3 (clone 3J23) and visualized with horseradish peroxidase (HRP)-conjugated anti-mouse antibody and HRP chemiluminescent substrate (Millipore).…”
Section: Methodsmentioning
confidence: 99%
“…The majority of infected persons could have either no symptoms or a very less mild sickness, which is hard to recognize as the cause of histoplasmosis [5]. The clinical symptoms generally occur only in a small number (around 1%) of the population when exposed with H. capsulatum spores [6]. Persons who are usually immuno-compromised and are unable to develop effective cell-mediated response are likely to develop symptomatic disease during the period of acute dissemination in body [5], which includes infant child, patients with HIV/AIDS, organ transplant recipients, and those with hematologic deficiencies, and also those patients, who are on corticosteroids drugs treatment [7].…”
Section: Introductionmentioning
confidence: 99%